Diabetic foot complications among Indigenous peoples in Canada: a scoping review through the PROGRESS-PLUS equity lens - Blanchette, Virginie; Patry, Jérôme; Brousseau-Foley, Magali; Todkar, Shweta; Libier, Solène; Leclerc, Anne-Marie; Armstrong, David G.; Tremblay, Marie-Claude (Frontiers in Endocrinology, 2023)
This is a provisional file, not the final typeset article Of 5,323 records identified, 40 studies were included in the review. The majority of studies focused on First Nations (92%), while representation of the Inuit population was very limited populations (< 3% of studies). LEA was the most studied outcome (76%). Age, gender, ethnicity, and place of residence were the most commonly included variables. Patient-oriented/centered research was mainly included in recent studies (16%). The overall quality of the studies was average. Data synthesis showed a high burden of DRFC among Indigenous populations compared to non-Indigenous populations. Indigenous identity and rural/remote communities were associated with the worse outcomes, particularly major LEA.This study provides a comprehensive understanding of DRFC in Indigenous peoples in Canada of published studies in database. It not only incorporates an equity lens and patient-oriented/centered research but also demonstrates that we need to change our approach. More data is needed to fully understand the burden of DRFC among Indigenous peoples, particularly in the Northern region in Canada where no data are previously available. Western research methods are insufficient to understand the unique situation of Indigenous peoples and it is essential to promote culturally safe and quality healthcare.Efforts have been made to manage DRFC, but continued attention and support are necessary to address this population's needs and ensure equitable prevention, access and care that embraces their ways of knowing, being and acting.